KELALAIAN SUAMI DALAM MENAFKAHI ISTRI KARENA PERILAKU KONSUMTIF: ANALISIS HUKUM ISLAM DI KELURAHAN LANGKAPURA BARU,KOTA BANDAR LAMPUNG - Sherina Kairunnisa Rusman; Zikri; Ahmad Ikhwani (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This research is motivated by the phenomenon of neglecting livelihood in households when husbands prioritize consumptive behavior such as collecting luxury goods over meeting family needs. This study aims to analyze the forms of neglect of livelihood that arise due to disproportionate use of assets, and examine the consequences and status from an Islamic legal perspective. The study was conducted using a descriptive qualitative approach to understand the social, economic, and dynamic conditions of families experiencing neglect of livelihood due to consumptive behavior. The results show neglect of basic family needs, a gap in perception between husband and wife regarding the fulfillment of livelihood, and the emergence of psychological stress and household disharmony. From an Islamic legal perspective, these actions fall into the categories of taqsir (negligence) and isrāf (wastefulness), which contradict the principle of qiwāmah and the objectives of sharia in protecting life and property. In conclusion, consumptive behavior that results in neglect of livelihood not only violates religious provisions but also has the potential to harm family welfare. Therefore, understanding livelihood priorities and strengthening education on financial management according to Islamic values ​​is essential